Ayurvedic Management of Papular Dermatosis (AYUSHDHARA, 2025)
Papular dermatoses are a group of skin disorders characterized by multiple small, raised papules, among which lichen nitidus is one of the uncommon variants. It is a rare, chronic inflammatory condition of the skin, mostly in children and young adults. It may cause considerable discomfort due to pruritus and may necessitate treatment for cosmetic or symptomatic relief. This case study explores the diagnosis and Ayurvedic management of a 17-year-old male patient with papular lesions on the scalp, for whom a probable diagnosis of lichen nitidus was considered based on clinical features. Management incorporated a Dosha-based approach along with Ayurvedic principles of Kushta Roga, using oral formulations and topical applications. The patient experienced symptomatic improvement, with reduced itching and complete resolution of lesions. This case highlights the potential role of Ayurvedic management in papular dermatoses and emphasizes the need for further exploration of Ayurvedic principles in their management through well-designed clinical studies.